Identification of key qualitative characteristics used to assess the significance of misstatements identified in the financial statements - Masiulevičius, Audrius (Buhalterinės apskaitos teorija ir praktika, 2022)
Financial statements may be misstated for quantitative reasons, such as mathematically incorrect reporting of assets, liabilities or other. Misstatements in the financial statements may also be qualitative. It is the qualitative characteristics of the misstatement that reflect the significance of the misstatement not for mathematical magnitude, but for other reasons, such as changes in profitability trends or illegal activities. To date, auditors have dedicated more attention to the quantitative characteristics of misstatements and the qualitative characteristics have not been adequately assessed. And although the problem is well known to scientists and practitioners, little action has been taken to date. The objective of the study reflected in this article is to identify the key qualitative characteristics that auditors should consider in deciding the significance of the misstatements identified in the financial statements. A list of fifteen key qualitative characteristics was compiled during the study and the completeness of the list was confirmed by an expert survey. The list of key qualitative characteristics will not only assist the auditors in deciding on the significance of the misstatements identified but may also be used in further research to deepen the scientific knowledge of the qualitative characteristics.
Keywords: Qualitative characteristics, materiality, financial statements, misstatements, audit.